O strukture sovremennogo sporta vysshikh dostizhenij i sotsialno-pravovom statuse sportsmenov-professionalov - Pereverzin, I. I.; Suslov, F. P. (Teorija i Praktika fiziceskoj Kul'tury, 2002)
The sport movement in the world continuously extended in XX century, despite of pessimistic estimations of some sociologists and philosophers, predicted the gradual decline of sports of the maximum achievements in connection with the negative tendencies accompanied its development. The purpose of the article was to reveal the structure of modern sports of the maximum achievements, the social and the legal status of athletes in the conditions of professionalization and commertialization of sports. The development of professional sports in Russia and in the countries of the CIS began to occur fast rates in conditions of transition of these countries to market relations. For this purpose the necessary legal preconditions which in Russia have found legal registration in the law "On physical culture and sports in the Russian Federation" gradually were created. That law establishes, that "professional sports are an enterprise activity which purpose is the satisfaction of interests of the professional sports organizations, athletes, selected sports by their profession, and spectators ". The organizational structure of professional sports is determined by specificity of each kind of sports and consists of professional sports leagues, associations, the unions which are included in officially recognized federation by any kind of sports, professional sports clubs, and also sports teams and the athletes-professionals concluding contracts when due hereunder with specified professional physical cultures.